2015
DOI: 10.1186/s13287-015-0187-x
|View full text |Cite|
|
Sign up to set email alerts
|

Roles of microRNA-34a targeting SIRT1 in mesenchymal stem cells

Abstract: IntroductionMesenchymal stem cell (MSC)-based therapies have had positive outcomes both in animal models of cardiovascular diseases and in clinical patients. However, the number and function of MSCs decline during hypoxia and serum deprivation (H/SD), reducing their ability to contribute to endogenous injury repair. MicroRNA-34a (miR-34a) is originally identified as a TP53-targeted miRNA that modulates cell functions, including apoptosis, proliferation, and senescence via several signaling pathways, and hence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 58 publications
(76 reference statements)
4
56
0
Order By: Relevance
“…The cells were treated with geraniin for 2 h prior to the addition of LPS and subsequently incubated for 24 h. Total protein was extracted, and western blot analysis was performed as previously described [20]. The blots were incubated with primary antibodies against nuclear factor kappa B p65 (NF-κB-p65), phospho-NF-κB-p65, IκB-α (Beyotime Institute of Biotechnology, Jiangsu, China), and SOCS1 (Cell Signaling Technology, Danvers, MA, USA) at 4°C overnight.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The cells were treated with geraniin for 2 h prior to the addition of LPS and subsequently incubated for 24 h. Total protein was extracted, and western blot analysis was performed as previously described [20]. The blots were incubated with primary antibodies against nuclear factor kappa B p65 (NF-κB-p65), phospho-NF-κB-p65, IκB-α (Beyotime Institute of Biotechnology, Jiangsu, China), and SOCS1 (Cell Signaling Technology, Danvers, MA, USA) at 4°C overnight.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Interestingly, several studies showed that miR-34a mimics increased, and antisense miR-34a inhibited, in vitro ROS production (Bai et al, 2011; Ferreira et al, 2014; S.-Z. Li et al, 2014; F. Zhang et al, 2015) in several cell lines, suggesting a direct role of miR-34a in oxidative stress.…”
Section: Mir-34a and Normal Tissue Radiation-induced Toxicitymentioning
confidence: 99%
“…Neuronal differentiation can occur through miR-34a that leads to decreased SIRT1 expression and DNA-binding of p53 in mouse neural stem cells (134). Furthermore, miR-34a under other conditions that increase the SIRT1 and FoxO3a pathways can result in mitochondrial dysfunction and activation of intrinsic apoptotic pathways that are detrimental to mesenchymal stem cells (135). …”
Section: Sirt1 Non-coding Rnas and Stem Cell Proliferationmentioning
confidence: 99%